Participating in a fruit and vegetable intervention trial improves longer term fruit and vegetable consumption and barriers to fruit and vegetable consumption: a follow-up of the ADIT study. Issue 1 (December 2015) - Neville, Charlotte; McKinley, Michelle; Draffin, Claire; Gallagher, Nicola; Appleton, Katherine; Young, Ian; Edgar, J; Woodside, Jayne
Abstract Background Fruit and vegetable (FV) based intervention studies can be effective in increasing short term FV consumption. However, the longer term efficacy of such interventions is still unclear. The aim of the current study was to examine the maintenance of change in FV consumption 18-months after cessation of a FV intervention and to examine the effect of participating in a FV intervention on barriers to FV consumption. Methods A follow-up of a randomised controlled FV trial in 83 older adults (habitually consuming ≤2 portions/day) was conducted. At baseline, participants were assigned to continue consuming ≤2 portions FV/day or consume ≥5 portions FV/day for 16-weeks. We assessed FV intake and barriers to FV consumption at baseline, end of intervention and 18-months post-intervention. Results At 18-months, mean FV intakes in both groups were greater than baseline. The 5 portions/day group continued to show greater increases in FV consumption at 18-months than the 2 portions/day group (p  < 0.01). At 18-months, both groups reported greater liking (p  < 0.01) and ease in consuming FV (p  = 0.001) while difficulties with consuming FV decreased (p  < 0.001). The 2 portions/day group reported greater awareness of FV recommendations at 18-months (p  < 0.001). Conclusions Participating in a FV intervention can lead to longer-term positive changes in FV consumption regardless of original group allocation. Trial registration Clinical Trials.govNCT00858728 .